2002
DOI: 10.1063/1.1504162
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the shape and indium distribution of low-growth-rate InAs quantum dots by cross-sectional scanning tunneling microscopy

Abstract: We present a cross-sectional scanning-tunneling microscopy investigation of the shape, size, and composition of InAs quantum dots in a GaAs matrix, grown by molecular beam epitaxy at low growth rate. From the dimensional analysis we conclude that the investigated quantum dots have an average height of 5 nm, a square base of 18 nm oriented along ͓010͔ and ͓100͔ and the shape of a truncated pyramid. From outward relaxation and lattice constant profiles we conclude that the dots consist of an InGaAs alloy and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
83
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(93 citation statements)
references
References 16 publications
9
83
0
1
Order By: Relevance
“…"100… substrate a function of GI for both substrates. The PL energy is dependent on the size of the dots, the strain, the quantum dot composition, 10 etc., and is shifted to higher energies ͑ϳ1.25 eV͒ in comparison with that of bulk InAs (0.4 eV, Ref. 11), mainly due to strong charge confinement.…”
Section: Resultsmentioning
confidence: 99%
“…"100… substrate a function of GI for both substrates. The PL energy is dependent on the size of the dots, the strain, the quantum dot composition, 10 etc., and is shifted to higher energies ͑ϳ1.25 eV͒ in comparison with that of bulk InAs (0.4 eV, Ref. 11), mainly due to strong charge confinement.…”
Section: Resultsmentioning
confidence: 99%
“…9 Both XRD and XSTM suggest that the In composition varies with height through the QDs, with pure InAs at the top of the QDs and progressively more Ga in the alloy towards the base of the QDs. 7,8 This alloying effect depends on growth conditions, particularly temperature 2 and growth rate. 10 In this letter we describe the use of medium-energy ion scattering ͑MEIS͒ to produce composition profiles of InAs QDs.…”
mentioning
confidence: 99%
“…A linear variation with height in the QDs is assumed as the simplest nonconstant composition. 7,8 The contribution of the WL is important, particularly at the leading edge of the energy spectrum. The WL is expected to be an InGaAs alloy of thickness 1-2 ML, 1 and indeed the optimized WL comprises a 2 ML thick In 0.05 Ga 0.95 As alloy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This can also be seen by the slight asymmetry in the relaxation profile of the InAs/GaAs QD. From X-STM and photocurrent experiments, it has been shown that low-growth rate InAs/GaAs QDs have an increasing indium concentration in the growth direction [47,48]. However, other groups have reported InGaAs QDs with laterally non-uniform indium compositions showing an inverted-triangle, trumpet or truncated reversed-cone shape [26,[49][50][51].…”
Section: 14 Filled States Topography X-stm Image Of (A) Three Qd Laymentioning
confidence: 99%